Membangun Kepercayaan yang Berkelanjutan di Era Disruptif Komunikasi: Perspektif Media dan Komunikasi Digital - Dharmajaya, Agung; Minangkabawi, Harmonis (Program Studi Ilmu Komunikasi, 2024)
The purpose of this research is to find out the factors that can build sustainable trust in the field of disruptive communication from the perspective of digital media and communication. This research uses qualitative research methods. The data collection technique in this research is done by literature study by exploring journals, books and other information relevant to the research. The data that has been collected is then analyzed in three processes, namely data reduction, data presentation and conclusion drawing. The results showed that building sustainable trust in the disruptive communication field is an ongoing challenge. Transparency, accountability, education and collaboration are important strategies to maintain credibility and trust. The case of the presidential election illustrates the impact of media and digital communications on public perception, and emphasizes the need for responsible practices. As the media landscape continues to evolve, addressing potential issues such as algorithmic bias and privacy concerns is critical to ensure trust in digital communications remains intact.